The Impact of Physical Activity on Digestive System Diseases - Bartłomiej Zabawa; Jakub Sadowski; Piotr Mól; Łukasz Stanisław Papież; Julia Dołęga; Karol Krzykawski; Tomasz Maciejczyk; Antoni Sieńko; Małgorzata Łabuś; Patrycja Hudzińska (Quality in Sport)
ABSTRACT